Pengaruh Sistem Pemerintahan Berbasis Elektronik (SPBE), Kepemimpinan Dan Budaya Organisasi Terhadap Kinerja Pegawai Biro Administrasi Pimpinan Sekretariat Provinsi Sumatera Barat - Dila Oktaviona; Eka Mariyanti (GLOBAL SCIENTS PUBLISHER, 2025)
This study evaluates the impact of the implementation of the Electronic-Based Government System (SPBE), leadership, and organizational culture on employee performance at the Bureau of Administrative Leadership, Regional Secretariat of West Sumatra Province. Using a quantitative approach, this research aims to assess the extent to which these three variables contribute to improving employee performance. Data were collected through a survey of 75 employees at the Bureau of Administrative Leadership using a total sampling method. Data processing and analysis were conducted using SPSS version 23 software with multiple linear regression analysis. The findings indicate that among the three variables examined, leadership has the most significant influence on employee performance. This suggests that effective leadership can enhance motivation, increase productivity, and instill greater work discipline within the bureaucratic environment.